Oral Meloxicam Administration in Sows at Farrowing and Its Effects on Piglet Immunity Transfer and Growth - Navarro, Elena; Mainau, Eva; de Miguel, Ricardo; Temple, Déborah; Salas, Marina; Manteca, Xavier (Frontiers in Veterinary Science, 2021)
Many factors can lead to an inadequate development of piglets during their first days of life, including poor maternal behaviour, which can be due to pain caused by farrowing, and reduced colostrum ingestion. This study investigates the action of meloxicam administrated orally at farrowing on piglet weight gain and immunity transfer. Thirty-five multiparous sows were divided into two groups and treated with 0.4 mg/kg of oral meloxicam (oral meloxicam group; n = 18) or with a mock administration (control group; n = 17). A total of 382 piglets were individually weighed on the farrowing day (day 0), as well as on day +9 and +20. Immunoglobulin G (IgG) and A (IgA) concentrations in serum of piglets and in sow's saliva, colostrum or milk were measured. Additionally, Interleukin-2 (IL-2), Interleukin-4 (IL-4) and Interferon gamma (IFN-ϒ) in serum of piglets and in sow's milk or colostrum were studied. All samples were obtained on days +1, +9 and +20. Piglets from sows in the oral meloxicam group tended to grow faster from day +9 to day +20 than piglets from control sows, and this difference was significant for piglets with low body weight (BW) at birth (p = 0.0682 and p = 0.0439 respectively). Oral meloxicam group sows showed a significant increase in colostrum IgA levels and a tendency in colostrum IgG levels compared with control sows on day +1 (p = 0.0039 and p = 0.0513, respectively). IgA levels in serum of piglets from the oral meloxicam group were significantly higher than in the control group on day +1 (p = 0.0177). Furthermore, IL-2 and IL-4 levels in the serum of piglets from sows in the oral meloxicam group were significantly higher than in the control group on days +9 (p = 0.0021 and 0.0012 respectively) and +20 (p = 0.0040 and 0.0776 respectively). The administration of meloxicam orally at the beginning of farrowing in multiparous sows increased immunoglobin and cytokine concentrations in colostrum and improved both humoral and cellular immune response of piglets. Pre-weaning growth of piglets, especially in piglets born with a low BW, improved in the meloxicam treated group.